Marketing Analysis and Market Development of Local Food Products of Mie Sagu Negeri Rutong Business Group, South Leitimur District, Ambon City - Alvian Sapulette; Fauzia Tutupoho; Jeffry Malakauseya (Politeknik Negeri Semarang, 2025)
Maluku is rich in carbohydrate-producing plants. In general, carbohydrates are obtained from farmers' rice fields and gardens, such as: rice, wheat, tubers, corn, etc., as well as sago plants. Negeri Rutong, South Leitimur subdistrict, Ambon City, an agrotourism village where there is a large sago forest, as well as a business group that is part of the MSME group that produces sago flour and there is also a group that produces sago noodles. The Rutong State sago flour production business group is one of the suppliers of raw materials to one of the entrepreneurs producing sago noodle products in Ambon City. Meanwhile, the Rutong country's sago noodle producing business group has not yet developed market development which has one permanent business place providing sales with activities serving consumers in selling sago noodles or offering sales of fried sago noodles/gravy. From the results of an interview dialogue with one of the state or village assistants who is in charge of economic development and empowerment, the sago noodle business group has not yet developed its business optimally, but their activities are in selling noodles to consumers if there is an event in the country or there is a message from the group. The aim of this research is to determine the state of the internal and external environment of the sago noodle business group and to map the marketing strategy for local food products using method stages, namely conducting interviews with the business group to obtain information and data, then tabulating the data, identifying SWOT, designing a marketing mix strategy Maluku kaya akan tanaman penghasil karbohidrat. Pada umumnya karbohidrat itu diperoleh dari sawah dan kebun petani seperti : beras, gandum, umbi-umbian, jagung, dan lainnya, juga pada tanaman sagu. Negeri Rutong kecamatan Leitimur Selatan Kota Ambon desa agrowisata dimana ada hutan sagu yang luas demikian juga ada kelompok usaha yang tergabung dalam kelompok UMKM yang memproduksikan tepung sagu dan juga ada kelompok yang menghasilkan mie sagu. Kelompok usaha produksi tepung sagu Negeri Rutong menjadi salah satu supplai bahan baku kepada salah satu pengusaha penghasil produk mie sagu di kota ambon. Sementara kelompok usaha penghasil mie sagu negeri Rutong belum berkembang dalam pengembangan pasar yang memiliki satu tempat usaha parmanen menyajikan penjualan dengan aktifitas melayani konsumen dalam menjual mie sagu ataupun menawarkan penjualan mie sagu goreng/kuah. Dari hasil dialog wawancara salah satu pendamping negeri atau desa yang membidangi pengembangan ekonomi dan perberdayaan bahwa kelompok usaha mie sagu belum mengembangan usaha secara optimal namun aktifitas mereka dalam menjajakan mie kepada konsumen kalaua itu ada acara di negeri atau ada pesan dari kelompok. Tujuan penelitian ini adalah mengetahui keadaan lingkungan internal, eksternal dari kelompok usaha mie sagu dan melakukan pemetaan strategi pemasaran produk pangan lokal dengan tahapan metode yaitu melakukan wawancara dengan kelompok usaha mendapatkan informasi dan data kemudian dilakukan tabulasi data, mengidentifikasi SWOT, mendesain strategi marketing mix